Potential of Bioethanol Production from Local Agricultural Waste in North Maluku - Hi. Luth, Muhamad Sahman; Muhamad Saleh, Erna Rusliana; Albaar, Nurjanna (Sangia Research Media and Publishing, 2020)
The problem of the world energy crisis facing many countries, including Indonesia, can be overcome by using alternative energy sources to be used as fuel such as bioethanol. North Maluku is one of the regions in Indonesia that has a lot of agricultural products including waste. This agricultural waste contains a lot of carbohydrates which have the potential to be processed into bioethanol. This study aims to review research related to bioethanol production from agricultural waste and see the potential for bioethanol production from agricultural waste in North Maluku. This research method is written based on literature study. Sources of data in this study came from: 1). Related research journal. 2). Related institutions (BPS Maluku Utara). Data processing is carried out in calculating the potential bioethanol that can be produced. The results of the study showed that there were 190,276,660,746 tons of waste in North Maluku. If converted into bioethanol, there will be 10,630,272.41 kiloliters of bioethanol. Thus, North Maluku has the potential for bioethanol production.